Assessment of seismic behaviour and safety of a masonry heritage - TÜRK, AHMET MURAT (Selçuk Üniv, Meram Tıp Fakultesi, 2019)
Turkey is a highly seismic country where numerous major earthquakes have devastated or damaged the existing historic structures owing to there is a large number of historical structures, mostly religious ones like mosques, and churches. The minarets are essential parts of mosques and there are many of these historic structures across the country which were built since Seljuq Empire started to rule the Anatolia and followed by Ottomans. As Turkey located in a highly active seismic zone, the possible damage of the minarets, the tallest part of the mosques, should be examined and the safety measures, in terms of seismic retrofit, should be considered. It is engineering communities' responsibility to satisfy the longevity of these existing heritages by the help of science and knowledge. To realize this objective, a case study is planned which addresses the problem of seismic capacity of a stone masonry minaret as a part of the architectural heritage in Istanbul, and a typical historical mosque is chosen. Mathematical model of the minaret is prepared in order to obtain possible deformation profile, lateral displacements, free vibration modes and most likely failure modes under seismic excitation by using response spectrum analysis. Most recent developments in the in-situ testing of structures and computational procedures for structural analysis have made reaching to the important results about the behaviour of the old masonry structures. The numerical results have shown that the greatest damage accumulated near the shoe region and the lower part of the shaft. The evaluation of these results is promising in terms of seismic safety of these heritages with minimized intervention on the structure without compromising the authentic view and function.
Keywords: Historical; Heritage Structure; Minaret; Seismic; Masonry; Performance